EFFECT OF PHOSPHORUS LEVELS ON YIELD AND QUALITY OF FODDER COWPEA VARIETIES UNDER RAINFED CONDITIONS - S, TIRUMALA REDDY (The Journal of Research ANGRAU, 2026)
The experiment was conducted during kharif, 2018-19 on red loam soils of RegionalAgricultural Research Station, Tirupati. The experiment was laid in the randomized block designwith factorial concept and each treatment replicated thrice. The results showed that the highergreen fodder yield (21,054 kg ha-1) and dry fodder yield (3,473 kg ha-1) was obtained with MFC08-14 variety. Significantly higher crude protein content (12.15%) was registered with APFC 101 variety, while the difference in crude fibre content among the varieties were found non-significant.Among the different levels of phosphorus, application of 60 kg P2O5/ha recorded significantlyhigher green fodder yield (21,590 kg/ha). Crude fibre content was not significantly influencedeither by varieties or different levels of phosphorus application under rainfed conditions ofSouthern Zone of Andhra Pradesh.